2020
DOI: 10.3390/molecules25204617
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Role of Neoxanthin in Plants and Algae

Abstract: Light is a paramount parameter driving photosynthesis. However, excessive irradiance leads to the formation of reactive oxygen species that cause cell damage and hamper the growth of photosynthetic organisms. Xanthophylls are key pigments involved in the photoprotective response of plants and algae to excessive light. Of particular relevance is the operation of xanthophyll cycles (XC) leading to the formation of de-epoxidized molecules with energy dissipating capacities. Neoxanthin, found in plants and algae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 106 publications
0
19
1
Order By: Relevance
“…The diadinoxanthin cycle includes interconversions of acetylenic (having one triple bond) xanthophylls. With excessive light, diadinoxanthin is converted to diatoxanthin, and with low light, the opposite reaction is observed [115,118,119].…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…The diadinoxanthin cycle includes interconversions of acetylenic (having one triple bond) xanthophylls. With excessive light, diadinoxanthin is converted to diatoxanthin, and with low light, the opposite reaction is observed [115,118,119].…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 99%
“…Carotenoids play an important role in the photosynthesis processes of microalgae, as additional pigments, as well as in the mechanisms of photoprotection when exposed to high intensity light. Photoprotective mechanisms involving carotenoids in algae are quite diverse and have been discussed in detail in a number of recent works [67,70,115,116].…”
Section: Production Of Carotenoids When Changing Light Intensitymentioning
confidence: 99%
“…PCA scores plot were performed using the complete phospholipids dataset (normalized XIC areas) while for heatmaps/clustering analysis the 25 molecular species that most contributed to differentiation between treatments were selected (PLS-DA vip). Holzwarth et al, 2009;Giossi et al, 2020). For these reasons, the rearrangement of the MGDG pool observed in our study could reflect significant changes happening in the thylakoid membrane environment of Bryopsidales, possibly influencing the interaction between pigment and proteins within the SCP.…”
Section: Pigment-lipid Interactions Within the Thylakoid Membranesmentioning
confidence: 66%
“…In most algae and plant taxawith the only exception of the ancient green alga lineages of Mesostigmatophyceae (Yoshii et al, 2003) and Bryopsidales (Qin et al, 2015)--the cis isomer of neoxanthin (c-Neo) represents the sole molecular form associated with antenna complexes, while t-Neo is not associated with light harvesting or photoprotection (Takaichi and Mimuro, 1998). Hence, the involvement of t-Neo in photoprotection could represent a unique mechanism of Bryopsidales (Giossi et al, 2020). The presence of such photoprotective activity could represent a safety valve for the dissipation of excess excitation energy under higher irradiances, particularly relevant for these algae that lack a functional xanthophyll cycle (Franklin et al, 1996;Raniello et al, 2004Raniello et al, , 2006Cruz et al, 2015;Christa et al, 2017;Giovagnetti et al, 2018), an important and ubiquitous photoprotection mechanism in aquatic and terrestrial oxygenic phototrophs (Latowski et al, 2011;Goss and Lepetit, 2015).…”
Section: Pigment Contribution To Excess Energy Regulationmentioning
confidence: 99%
“…These contributions provide a comprehensive view of some of the most relevant compounds in photoprotection. Giossi et al explore the biological role of neoxanthin, a pigment found in plants and algae [ 8 ]. The review from Abiola and colleagues focuses on the use of ultrafast spectroscopy and computational methods to understand the photoprotective mechanism of some natural compounds [ 9 ].…”
mentioning
confidence: 99%